Ersu. (20th July 2015) - Chirkova, Katia; Wang, Dehe; Chen, Yiya; Amelot, Angélique; Kocjančič Antolík, Tanja
Abstract : The Ersu language (/ - x ò/, 尔苏语 ěrsūyǔ, ISO-639 code ers ) is spoken by approximately 16, 800 people who reside in five counties in Sichuan Province (四川省) in the People's Republic of China: (i) Ganluo (甘洛县), and (ii) Yuexi (越西县) counties of Liangshan Yi Autonomous Prefecture (凉山彝族自治州), (iii) Shimian (石棉县) and (iv) Hanyuan (汉源县) counties of Ya'an Municipality (雅安市), and (iv) Jiulong (九龙县, Written Tibetan, hereafter WT brgyad zur ) county of Ganzi (甘孜, WT dkar mdzes ) Tibetan Autonomous Prefecture. Ersu has two closely related sister languages: Lizu (/li 55 -zu 55 -h ũ 55 / or /ly 55 -zu 55 -h ũ 55 /, 里汝语 lǐrǔyǔ or 栗苏语 lìsūyǔ ) and Duoxu (/do 33 -ɕu 33 -na 31 /, 多续语 duōxùyǔ or 多须语 duōxūyǔ ). Lizu is spoken in the neighbouring counties of (i) Muli Tibetan Autonomous County (木里藏族自治县, WT smi li rang skyong rdzong ), (ii) Mianning (冕宁县), and (iii) Jiulong; whereas Duoxu is spoken in the county of Mianning, all in Sichuan province (see the map in Figure 1).